Inside Back Cover: Unwrapping Core–Shell Nanowires into Nanoribbon‐Based Superstructures (Angew. Chem. Int. Ed. 43/2013). Issue 43 (9th October 2013) - Pevzner, Alexander; Davidi, Guy; Peretz‐Soroka, Hagit; Havivi, Ehud; Barkay, Zahava; Popovitz‐Biro, Ronit; Khatchtourints, Artium; Patolsky, Fernando
<x xml:space="preserve">Abstract</x> Sacrificial core–shell nanowire precursors can be readily shape‐transformed into semiconductor nanoribbon materials by a combination of bottom‐up and top‐down procedures, as described by F. Patolsky et al. in their Communication on page 11298 ff. This unexpected nanowire‐to‐nanoribbon transformation process allows the synthesis of superflexible nanoribbons of desired dimension, shape, and chemical composition.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>